Phytochemical analysis and antibacterial activity of raspberry (Rubus idaeus) fruit extract against Gram-negative multi-drug resistant bacteria from clinical isolates - Maslov, O.Y.; Komisarenko, M.A.; Ponomarenko, S.V.; Osolodchenko, T.P.; Kolisnyk, S.V.; Polishchuk, S.I. (Chemical Bulletin of Kazakh National University, 2025)
The basic therapy for microbial infections involves the application of antibiotics. However, overuse of antibiotics has become the major factor for the emergence and dissemination of multi-drug resistant strains. The purpose of our work was to study the phytochemical composition of a thick extract of raspberry fruits, as well as to investigate in vitro and in silico antibacterial activity against clinical multidrug-resistant strains of A. baumannii, P. aeruginosa, K. pneumoniae and E. cloacae. The quantification of biologically active substances (BAS) was accomplished with spectrophotometric, titrimetric and HPLC methods of analysis; antimicrobial effects were evaluated by the well diffusion method, whereas minimum inhibition concentration was determined by well plate method. The total content of phenolic compounds was 0.60 and 10.10%, organic acids – 4.60 and 1.60% for raspberry fruit thick and green tea leaf extract. The total content of anthocyanins in the raspberry fruit thick extract was 110.0 mg/100 g, where cyanidin-3-O-sophoroside was dominated (52.14±1.04 mg/100 g). Theoretical studies have shown that neither a single antibiotic nor anthocyanins are highly effective in inhibiting all antimicrobial mechanisms of resistant Gram-negative bacteria. The thick raspberry fruit extract actively inhibits all resistant strains of A. baumannii, K. pneumoniae, P. aeruginosa and E. cloacae. These findings have shown that to inhibit resistant strains of bacteria, you need to use only a complex drug or dietary supplements of raspberry together, and in turn, herbal medicines are a “lifeline” for their creation and there is a chance of old antimicrobial drugs back in life.